Discrete-time sliding mode control of input-delay systems applied on a power generation system - Ribeiro, J. M S [UNESP]; Garcia, J. P F [UNESP]; Jacomeli, J. R. [UNESP]; Garcia, L. M C F [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2006)
This paper presents two discrete sliding mode control (SMC) design. The first one is a discrete-time SMC design that doesn't take into account the time-delay. The second one is a discrete-time SMC design, which takes in consideration the time-delay. The proposed techniques aim at the accomplishment simplicity and robustness for an uncertainty class. Simulations results are shown and the effectiveness of the used techniques is analyzed. © 2006 IEEE.
Keywords: Discrete Sliding Mode Control; Discrete-time; Discrete-time sliding mode control; Input delays; International symposium; Power-generation systems; Continuous time systems; Control theory; Delay circuits; Delay control systems; Industrial electronics; Sliding mode control; Time delay; Discrete time control systems